Strategic planning practices, entrepreneurial orientation, environmental uncertainty and internationalization of small and medium enterprises - Mohd Faudzi, Musa (2015)
The understanding on factors contributing to internationalization of small and medium enterprises (SMEs) in Malaysia is still lacking, and that the SME contribution to the country’s export is still small compared to those neighbouring countries and most of the developed countries. Therefore, the objective of this study is to empirically test the relationships between strategic planning practices, entrepreneurial orientation, and environmental uncertainty on the internationalization of SME’s in Malaysia. This study emanated from the fact that there is limited study in this area and more research should be conducted especially in the context of Malaysia. Based on the theoretical consideration a model was proposed and hypotheses were developed. Survey questionnaires were used in the data collection and a total of 250 useable responses were received from the exporting SMEs in Malaysia. Partial Least Squares Structural Equation Model (PLS-SEM) was employed in the data analysis. The findings revealed that strategic planning practices and entrepreneurial orientation have significant and positive relationships with the internationalization of SMEs. The results further found the moderating role of environmental uncertainty in the relationships between strategic planning practices and internationalization as well as between entrepreneurial orientation and internationalization of SMEs. These findings also support the resource based view which emphasizes the importance of internal capability of a firm as an influenced driver in achieving export performance and competitive advantage. Thus this study sheds some light on an understanding and evaluation of the relationship between strategic planning practices, entrepreneurial orientation and environmental uncertainty on the internationalization of SMEs in Malaysia. Finally, the study concludes with some theoretical and practical implications as well as the limitations and directions for future research